Clinical assessment of overuse injury risk in office workers participating in weekend tennis activities - Kutanggas, Rivo Christian; Setyawan, Yuswanto (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
This study examines the correlation between tennis activity and overuse injury risk among office workers, a population increasingly involved in high-intensity weekend sports despite predominantly sedentary weekday routines. Using a cross-sectional design, data were collected from 112 office workers aged 25–55 years who regularly played tennis. A structured questionnaire and physical assessment were used to evaluate injury incidence, tennis activity patterns, and occupational physical activity levels. The results showed a statistically significant association (p < 0.05) between the frequency and intensity of weekend tennis and the prevalence of overuse injuries, particularly in the shoulder, knee, and elbow. Office workers with low weekday physical activity and inadequate warm-up routines exhibited a higher risk of injury. These findings highlight the mismatch between limited baseline fitness and abrupt physical exertion, contributing to musculoskeletal strain. The study emphasizes the importance of continuous conditioning, proper warm-up routines, and injury-prevention education tailored to recreational athletes in sedentary professions. Future research should explore longitudinal designs, incorporate more detailed biomechanical or clinical assessments, and evaluate intervention-based programs to better understand causal mechanisms and effective prevention strategies for overuse injuries in weekend athletes.